(untitled) (Emergency Care Journal, 2023)
Rugby-related renal trauma is rare and identification of a young patient with renal trauma secondary to sports who requires observation versus further radiological evaluation in the emergency department (ED) poses a diagnostic challenge. We report a case of a 16-year-old girl who presented to the ED with abdominal pain after being tackled during a game of rugby. Examination revealed tenderness over the right lateral lower ribs and right flank. Blood tests were normal and bedside ultrasound did not show any free intraperitoneal fluid. Urinalysis showed gross hematuria. She was pain-free after analgesia but had a syncopal episode in the ED. A computed tomography (CT) scan of the abdomen and pelvis showed a complex right lower pole renal laceration and she was admitted to the Intensive Care Unit. She remained stable and was discharged. Assessment with urinalysis, hematocrit, and creatinine is required during the evaluation of a patient with suspected renal trauma. CT scan is the imaging modality for the diagnosis and grading of renal injury. Conservative treatment is the mainstay of therapy, but some patients require angioembolization of surgical intervention. Patients must discuss with their physician regarding the optimal timing of return to rugby. Rugby-related renal trauma is rare and poses a challenge for emergency physicians regarding their evaluation and management in the ED. AAST-OIS grading of renal trauma on CT imaging helps guide appropriate management decisions.